Systematic study of effect of particle size distribution in a dense medium cyclone by Johnson's SB function. (15th May 2016) - Chen, Jiang; Chu, Kaiwei; Zou, Ruiping; Yu, Aibing; Vince, Andrew; Barnett, G.D.; Barnett, P.J.
Graphical abstract: A CFD–DEM model is used to systematically study the effect of particle size distribution in a DMC. The figure shows the flow pattern of coal particles in the DMC with different distribution parameter σ j when the M:C ratio is 5.6 (at t = 30.0 s): (I), coal particle density at a central vertical slice (of thickness 10% Dc) of the DMC; and (II), particle–particle force at a central section of the DMC (the section is normal to the inlet of the DMC). Highlights: A CFD–DEM model is used to study the effect of particle size distribution in a DMC. Johnson's SB function is employed to describe the particle size distribution. The effect of particle size distribution on DMC performance is quantified. The microscopic structure of the flow is analysed to elucidate the underlying mechanism. Abstract: Dense medium cyclone (DMC) is a high-tonnage device that is widely used to upgrade run-of-mine coal in the 0.5–50 mm size range. It is known that the performance of a DMC depends on the coal particle size distribution but quantitative relationships have not been established yet. In this work, the effect of the particle size distribution in a DMC is studied in detail using the combined Computational Fluid Dynamics (CFD) and Discrete Element Method (DEM). In particular, Johnson's SB function, which is capable of representing a wide range of size distributions, is employed to describe the particle size distribution of coal. The function has two parameters, i.e., particle median size d 0.5 and distribution parameter σ j, for a given size range. It is found that for a constant σ j, the operational head and medium differential decrease dramatically, and the separation efficiency deteriorates rapidly when d 0.5 increases from 6 to 40 mm. For a constant d 0.5, the DMC performance is sensitive to σ j, particularly when d 0.5 and σ j are small. Both the medium differential and split decrease at first and then almost remain constant as σ j increases from 0.4 to 1.0, and the separation performance follows the similar trend as well. The simulation results are also analysed in terms of medium and particle flow patterns, particle–fluid, particle–particle and particle–wall interaction forces to elucidate the underlying mechanism. For example, the decrease of pressure gradient force and viscous drag force represents the loss of swirling energy and then contributes to the drop of operational pressure and worse separation efficiency. The results should be useful to better design and control DMC operations, particularly for various coal types with different particle size distributions.